Comparison of Premixed with Sequential Administration of Intrathecal Morphine and Hyperbaric Bupivacaine for Lower Segment Caesarean Section - Jahanara; Koshyari, Harish Singh; Asthana, Veena; Nautiyal, Ruchira (Academia Anesthesiologica International, 2020)
Background: Adequate pain relief is considered as a basic human right .In obstetrics patients, using low dose opioids (Morphine, Fentanyl, sufentanil) in neuraxial blockade is effective method for anaesthesia and postoperative analgesia in LSCS and nearly no danger to parturient or unborn. Subjects and Methods: Keeping in mind the difference in the baricties of commonly used hyperbaric bupivacaine and morphine, we conducted a single blind randomized controlled trial on 156 full term parturient scheduled for elective and emergency LSCS under SAB and on the technique of intrathecal administration of drug parturients were divided into 3 groups. GROUP 1 (n=52) - Hyperbaric bupivacaine (0.5%) 9mg (1.8ml) + morphine 200mcg (0.2ml) as a mixture GROUP 2 (n=52)-Hyperbaric bupivacaine (0.5%) 9mg (1.8ml) + Morphine 200mcg (0.2ml) administered after bupivacaine GROUP 3 (n=52)-Hyperbaric bupivacaine (0.5%) 9mg (1.8ml) + Morphine 200mcg (0.2ml) administered before bupivacaine. We observed for block characteristics, maternal hemodynamics and neonatal outcome. Results: In our study, duration of analgesia was clinically prolonged in all the groups. The block characteristics were comparable between the groups.These beneficial effects were not accompanied by any major hemodynamic instability or adverse effects and no untoward effect on the newborn. Conclusion: Premixed and sequential administration of IT morphine with hyperbaric bupivacaine were comparable in terms of quality of subarachnoid block maternal hemodynamic and neonatal outcome.